Why we need signed poetry in bilingual education - Sutton-Spence, Rachel (Educar em Revista, 2014)
A truly bilingual and bicultural education for deaf children requires them to learn about the deaf art-form of sign language poetry. In this article I outline the advantages and challenges of doing this. Reviewing the scarce literature on teaching deaf children signed poetry, whether translated or original, I relate it to the use of literature in L2-learning settings. Reflections of deaf teacher-poets from the UK show that deaf children readily relate to signed poetry, and with informed language focus from teachers it helps them to develop a range of language skills, and express their emotions. Barriers to this, however, include lack of training and awareness for both deaf and hearing teachers – even when the teachers are poets.